Vida Saludable: Examinando su Glucosa en la Sangre - Jennifer Hillan (EDIS)
FCS8811-SPAN, a 2-page fact sheet by Jennifer Hillan, is the Spanish version of "Healthy Living for Elders: Checking Blood Glucose" (FCS8811/FY868). It will help diabetics understand when and how to check their blood glucose levels. Also provides a sample log for keeping track of readings. Published by the UF Department of Family, Youth and Community Sciences, December 2006.